River Tourism in Bangladesh: Present Status and Future Prospects (Global Journal of Management and Business Research, 2023)
River tourism is quite different from the conventional tourism concept which is based on rivers Bangladesh has great potential to flourish in this sector Bangladesh is already famed as a riverine country A good number of tourists are interested in river tourism in Bangladesh Though there is huge potential for Bangladesh to become a prominent destination for river tourism but still it is untapped due to various challenges This study analyzed the existing river tourism sector of Bangladesh to explore the potentialities and challenges of this sector The study revealed that there are some challenges to gaining success in the development of river tourism Lack of skilled manpower safety and security issues lack of tourism infrastructure and inadequate funding are some remarkable challenges Based on the findings the paper suggested several recommendations for the development of river tourism in Bangladesh
Keywords: river tourism; major challenges; economic development; tourism growth